2022
DOI: 10.1212/wnl.0000000000200382
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Perilesional Neuroplastic Recruitment in Chronic Poststroke Aphasia

Abstract: Background and ObjectivesA prominent theory proposes that neuroplastic recruitment of perilesional tissue supports aphasia recovery, especially when language-capable cortex is spared by smaller lesions. This theory has rarely been tested directly, and findings have been inconclusive. Here, we test the perilesional plasticity hypothesis using two fMRI tasks in two groups of patients with prior aphasia diagnosis.MethodsTwo cohorts totaling 82 chronic left-hemisphere stroke patients with prior aphasia diagnosis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Additionally, understanding the role of spared left-hemispheric tissue in language recovery requires considering inter-individual variability and comparing to baseline activity in healthy controls. A recent study found no support for the perilesional neuroplastic recruitment hypothesis in aphasia, i.e., no enhanced activity in brain areas surrounding individual lesions, but some evidence supporting recruitment of brain regions distant to the lesion (DeMarco et al, 2022). Further studies employing individualized approaches, to investigate language network reorganization, treating individual differences as a variable of interest, are imperative in understanding language network reorganization in aphasia (Seghier and Price, 2018).…”
Section: Normalized Activity Of the Left-hemispheric Language Network...mentioning
confidence: 97%
See 1 more Smart Citation
“…Additionally, understanding the role of spared left-hemispheric tissue in language recovery requires considering inter-individual variability and comparing to baseline activity in healthy controls. A recent study found no support for the perilesional neuroplastic recruitment hypothesis in aphasia, i.e., no enhanced activity in brain areas surrounding individual lesions, but some evidence supporting recruitment of brain regions distant to the lesion (DeMarco et al, 2022). Further studies employing individualized approaches, to investigate language network reorganization, treating individual differences as a variable of interest, are imperative in understanding language network reorganization in aphasia (Seghier and Price, 2018).…”
Section: Normalized Activity Of the Left-hemispheric Language Network...mentioning
confidence: 97%
“…Most research in aphasia focused on the chronic stage (>6 months) post-stroke, characterized by a more stable language profile in IWA (Johnson et al, 2019). Both longitudinal and cross-sectional studies predominantly indicate optimal language recovery through normalization of activation in the left-hemispheric language network (Warren et al, 2009; Crinion et al, 2006; DeMarco et al, 2022; Saur et al, 2006; Stockert et al, 2020; Szaflarski et al, 2011, 2013; Griffis et al, 2017b; Fridriksson, 2010; Pillay et al, 2018; Wilson and Schneck, 2021; Li et al, 2022). The preservation of lesion-free tissue in left hemisphere language regions emerges as a crucial factor in facilitating language recovery (Fridriksson, 2010; Griffis et al, 2017a; Sims et al, 2016; Wilson and Schneck, 2021).…”
Section: Introductionmentioning
confidence: 99%